Discoveries in western Tibet and the western Himalayas: essays on history, literature, archaeology and art : PIATS 2003, Tibetan studies, proceedings of the Tenth Seminar of the International Association for Tibetan Studies, Oxford, 2003 - Heller, Amy; Orofino, Giacomella (Brill's Tibetan studies library 1568-6183, 2007)
Preliminary Materials /A. Heller and G. Orofino --Defining Zhang Zhung Ethnicity: An Archaeological Perspective From Far Western Tibet /Mark Aldenderfer --Newly Discovered Early Buddhist Grottos In Western Tibet /Huo Wei --The Architecture Of The Empty Shells Of Nyar Ma /Gerald Kozicz --The Divine Palaces Of The Buddha: Architectural Frames In Western Himalayan Art /Marialaura Di Mattia --From Archaeological Discovery To Text Analysis: The Khor Chags Monastery Findings And The Mañjusrïnämasamgïti Fragment /Giacomella Orofino --Preliminary Remarks On The Manuscripts Of Gnas Gsar Dgon Pa In Northern Dolpo (Nepal) /Amy Heller --Poetical Prefaces Of Manuscripts From Western Tibet /Elena De Rossi Filibeck --The Gu Ru Lha Khang At Phyi Dbang: A Mid-15th Century Temple In Central Ladakh /Erberto Lo Bue --Remarks On The Foundation And History Of Bsam Gling Dgon Pa /Geshe Wangyal --'Jag 'Dul--A Bon Mountain Pilgrimage In Dolpo, Nepal /Marietta Kind --Socio-Economic Organisation Of Village Communities And Monasteries In Spiti, H.P., India: The Case Of A Religious Administrative Unit (Chos Gzhis) /Christian Jahoda.